THE IMPORTANCE OF MRI IN THE RADIATION DIAGNOSIS OF OVARIAN CANCER - Olimov Sardorbek (Zamonaviy ta’lim va tilshunoslik rivoji, 2026)
Ovarian cancer is one of the most serious malignant diseases of the female reproductive system. Due to the absence of specific symptoms in the early stages, the disease is often diagnosed late. This study evaluates the diagnostic capabilities of magnetic resonance imaging (MRI) in the differential diagnosis of ovarian tumors. A retrospective analysis demonstrated that MRI provides valuable information regarding tumor morphology, extent of spread, and signs of malignancy. The findings confirm the important role of MRI in the early detection of ovarian cancer and in selecting appropriate treatment strategies.